Pengaruh Pupuk Kompos Limbah Kulit Kakao terhadap Pertumbuhan Tanaman Kangkung Darat (Ipomoea reptans Poir.) - Sutriani Kaliu; Erfina Erfina; Irma Indriana (Populer: Jurnal Penelitian Mahasiswa, 2025)
Cocoa (Theobroma cacao L.) is a plantation crop that produces cocoa shell waste, and is an alternative as compost fertilizer. Water spinach is a type of vegetable that is widely consumed, but its productivity has decreased. It is necessary to increase plant production by providing additional nutrients by using cocoa shell waste as fertilizer. This research aims to determine the effect of cocoa shell waste compost on the growth of land kale plants. Research methods, namely (RAK); 5 treatments and 4 replications consisting of; P0(control), P1(100gr/polybag), P2(200gr/polybag), P3(300gr/polybag), and P4(400gr/polybag. Parameters observed for growth included; plant stem height, number of leaves and wet weight, then The data was tested using (ANOVA) and continued with the test (BNT) with a level of 5%. The results of the ANOVA test showed that the height growth of land kale plants in the treatment had a very significant effect on the 200g dose of fertilizer where Fcount>Ftable (11.7>3.11) while the group did not have a significant effect where Fcount <Ftable (0.39 < 3.11). significant where Fcount < Ftable (1.83 < 3.11) as well as in groups where Fcount < Ftable (2.1 < 3.11), and the highest wet weight was in treatment P2, namely 5 gr. Providing cocoa shell compost fertilizer at a concentration of 200 gr gave the best results in all observed parameters.